CGIAR Review 2018 CCAFS Case study - Pillot, Didier; Dugue, Marie-Jo (2018)
This review was commissioned to evaluate European Commission (EC) contributions to the CGIAR Research Programme (CRP) on Climate Change, Agriculture and Food Security (CCAFS) in 2013-2015. EC contributions were €2.5 million per year, which represented around 3% of the total budget of the CCAFS during this period. 2. The review is framed around evaluation of processes and tools which can lead to impact, and on the contribution of the CCAFS to building/enriching a theory of change around the challenges of adaptation to and mitigation of climate change by agricultural systems. The team considers that focusing on direct impact is however insufficient in the case of an International Agricultural Research Center, and that the contribution of the CCAFS to building scientific knowledge through actions is also part of the mandate. The review focuses on three programmes in the West and East African regions: the Climate-Smart Villages, an emblematic programme which is widely reproduced in all CCAFS regions, the Climate Information Services in Senegal (which is supposed to be key for adaptation purposes) and the Dairy NAMA in Kenya (which is assumed to impact significantly on mitigation). Data collection was based on documentary analysis, site visits in Kenya and Senegal with direct field observations and interviews of selected partners and target stakeholders, and visits to the CCAFS Programme Management Unit in Wageningen. Due to the importance given to adapt to local specificities (institutionally and ecologically), the findings directly connected to the local environment might have been slightly different in South-East or South Asia, or Latin America, the three other regional programmes of the CCAFS. However the team believes this would not have affected the final conclusions nor the recommendations. 3. Established as a Challenge Programme in 2009, CCAFS has been fast-tracked for development as a CRP, and it resulted from direct efforts to build a transversal programme responding to a global challenge. It is now organized around five Regional Programmes and five thematic programmes (four Flagship Programs and one cross cutting theme) which are all transversal to Centres, which is rather not common within the CGIAR conventional structure of research. Although the organisation was slightly different in 2013-2015 than the one observed in August-September 2018, we consider this does not have a major impact on the conclusions of our assessment. 4. CCAFS’ Program Management Unit (PMU) is partly based at Wageningen University, partly at CIAT (Colombia). This central unit is extremely light, and a large delegation is given to the Regional or Thematic (FP) programmes. Some FP leaders are based at Universities or Research Institutes outside the CGIAR Centres. The Program Management Committee (PMC) comprises six members: the Program Director and five members selected between Regional Program Leaders and Flagship Leaders”.